HUBUNGAN POWER OTOT TUNGKAI TERHADAP HASIL SMASH PADA TIM BOLA VOLI LASKAR API-API BANDAR LAKSMANA - Fauzi, Fauzi; Vai, Aref; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aims to determine the relationship between arm andshoulder muscle power and smash performance in volleyball. The research uses acorrelation method. The study population consists of 12 volleyball players from the